Measurement of the prompt J/[psi] pair production cross-section in pp collisions at √s = 8 TeV with the ATLAS detector - Aaboud, Morad; Anders, Christoph; Andrei, George Victor; Antel, Claire; Baas, Alessandra Edda; Brandt, Oleg; Djuvsland, Julia Isabell; Dunford, Monica; Ferreira de Lima, Danilo Enoque; Geisler, Manuel Patrice; Giulini, Maddalena; Hanke, Paul; et al. (The European physical journal. C, Particles and fields, 2017)
The production of two prompt J/ψ mesons, each with transverse momenta pT>8.5 GeV and rapidity |y|<2.1, is studied using a sample of proton-proton collisions at s√=8 TeV, corresponding to an integrated luminosity of 11.4 fb−1 collected in 2012 with the ATLAS detector at the LHC. The differential cross-section, assuming unpolarised J/ψ production, is measured as a function of the transverse momentum of the lower-pT J/ψ meson, di-J/ψ pT and mass, the difference in rapidity between the two J/ψ mesons, and the azimuthal angle between the two J/ψ mesons. The fraction of prompt pair events due to double parton scattering is determined by studying kinematic correlations between the two J/ψ mesons. The total and double parton scattering cross-sections are compared with predictions. The effective cross-section of double parton scattering is measured to be σeff=6.3±1.6(stat)±1.0(syst) mb.
Gesehen am 31.01.2020
Im Titel steht der Buchstabe "s" unter dem Wurzelzeichen
Im Titel ist "psi" als griechischer Buchstabe dargestellt
*ATLAS Collaboration: M. Aaboud, C.F. Anders, V. Andrei, C. Antel, A.E. Baas, O. Brandt, J.J. Djuvsland, M. Dunford, D.E. Ferreira de Lima, M.P. Geisler, M. Giulini, P. Hanke, J. Jongmanns, E.-E. Kluge, M. Kolb, M. Kretz, A. Kugel, V.S. Lang, M. Lisovyi, K. Meier, H. Meyer zu Theenhausen, D.I. Narrias Villar, M. Sahinsoy, S. Schaetzel, A. Schoening, H.-C. Schultz-Coulon, D. Sosa, R. Stamen, P. Starovoitov, S. Suchek, M. Wessels [und 2823 weitere Personen]